The prevalence of thyroid disorder in pregnancy - Shah, Neelima; Shah, Prashant; Namala, Vyshnavi; Chowdhary, Deepannita Roy; Shah, Rachana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The development of maternal thyroid disorders during early pregnancy can influence the pregnancy outcome and fetal development. The present study was conducted to know the prevalence of thyroid disorders in the Indian pregnant population and the obstetric outcomes of those women suffering from thyroid disorders. Methods: The present study was conducted on 100 women who came for an antenatal check-up in the first trimester, with Singleton Pregnancy. A detailed history was taken followed by a thorough general physical examination. Patients were sent for TSH (Thyroid Stimulating Hormone) testing. Patients were sent for TSH (Thyroid Stimulating Hormone) testing. If TSH (Thyroid Stimulating Hormone) was deranged, then FT3 and FT4 levels were checked. Depending upon the FT3 and FT4 values they are grouped as subclinical/overt hypothyroidism or hyperthyroidism. Results: Most of the patients in the present study were from the age group 21 to 30 years. The prevalence of thyroid disorders in the present study was 38%, including hypo and hyperthyroidism. 28% of patients were found to be hypothyroid; 10% of patients were hyperthyroid. Conclusions: The prevalence of thyroid disorders, especially hypothyroidism (28%) was high. Further studies are needed to assess adverse effects on maternal and fetal outcomes. Routine antenatal thyroid screening should be done.